Pneumococcal infection in adults: burden of disease - Drijkoningen, J.J.C.; Rohde, G.G.U. (Clinical microbiology and infection, 2014)
To overview the present global burden of pneumococcal disease is important because new preventive measures such as the pneumococcal conjugate vaccine 13 are currently being evaluated. Pneumococcal disease is roughly divided into non-invasive and invasive disease. The burden of non-invasive pneumococcal disease in adults is mainly determined by community-acquired pneumonia. Pneumococcal pneumonia has high incidence rates and carries a high mortality risk, especially in the elderly. Within the cluster of invasive pneumococcal diseases, pneumonia also represents the most common infectious source. Incidence and mortality rates of both non-invasive and invasive disease have changed as a result of pneumococcal vaccination in children. However, especially elderly patients with comorbidities remain vulnerable to morbidity and mortality caused by pneumococcal disease. The current review summarizes the current knowledge on the epidemiology including outcome of the main clinical forms of pneumococcal disease, with a special focus on elderly patients. Furthermore, the economic burden and future vaccine strategies are briefly discussed.